Problem Mendasar Yang Muncul Dari Perkembangan Ilmu Di Bidang Hukum - Wawan Irawan (Syiar Hukum, 2017)
Recording the history of science can be traced back to thousands of years before Christ until now. Historical necessity gave birth to a wide range of concepts about the nature of science. Law as science has a distinctive character (suigeneris), that it is normative. Those characteristics caused some law scholars that do not understand the characteristics of jurisprudence have doubted law as a science. Doubt it caused more normative jurisprudence rather than empirical and his study object with respect to the guidance of behavior in a way that compliance is not entirely dependent on free will is concerned, but can be imposed by a public authority.Through science we generate new knowledge. Since the beginning of human civilization, Law has progressed in a continuous process. Progress toward understanding and managing the law-science problem seems to require disaggregating the questions. If we look carefully at what kind of "science" and what kind of "law," then perhaps we can get some analytic leverage. If we cut the general problem into little pieces, we can atleast ask more precisely what is problematic at which particular law-science interface.